IEEE Fellow Nominations Due 1 March. - Kurdahi, Fadi (Computer (00189162), 2007)
The article discusses the process of nominating some one for recognition as an IEEE Fellow. Some of the requirements are that a nominee must be a senior member at the time of nomination and must have been an IEEE member at any level for the previous five years. A nominator need not be an IEEE member, but the nominators cannot be IEEE staff or members of the IEEE Board of Directors, the Fellow Committee, the technical society, or council of evaluation committee. The article also gives advice of preparing a nomination and the web site with the complete list of regulations. The deadline for nomination is March, 1 2007.